Parties, Movements, Brokers: The Scottish Independence Movement. Issue 1 (1st June 2021) - McKeever, David
Abstract: This article is a study of the consequences of brokerage for movements, and particularly for the role of political parties within social movements. My findings indicate that brokerage creates opportunities for minor groups to play a crucial role in mobilization, something that comes at a cost to a movement's structure. I make my case with a study of brokerage in action, based on activist interviews, events data, and network data collected from the Scottish independence movement. Results demonstrate that the likelihood of the governing Scottish National Party participating in movement events only increases with the number of participating movement organizations. As the movement organizations transitioned from a referendum campaign to an autonomous movement, under-resourced peripheral groups took the lead in brokering the Nationalist movement.